POMEN TERAPEVTSKE KOMUNIKACIJE V AMBULANTNI OBRAVNAVI PACIENTA - Pušenjak, Klavdija ([K. Pušenjak], 2016)
Terapevtska komunikacija med medicinsko sestro in pacientom je zelo pomembna zaradi večjega zaupanja pacienta v potek zdravljenja, za kakovostno obravnavo pacienta in dober odnos med njima. V diplomskem delu je predstavljen pomen terapevtske komunikacije v ambulantni obravnavi pacienta, tehnike terapevtske komunikacije, ovire, ki nastanejo v sami komunikaciji med medicinsko sestro in pacientom ter vloga medicinske sestre v ambulantni dejavnosti. Therapeutic communication between the nurse and the patient is very important as it boosts the patient’s trust in the therapeutic process and improves the quality of their treatment as well as their relationship with the nurse. This thesis demonstrates the significance of therapeutic communication in outpatient treatment, techniques of therapeutic communication, problems occurring in the communication between the nurse and the patient and the role of the nurse in the outpatient service.